Non-invasive ventilation during surgery under neuraxial anaesthesia: a pathophysiological perspective on application and benefits and a systematic literature review (Anestezjologia Intensywna Terapia, 2019)
Unlike general anaesthesia, neuraxial anaesthesia (NA) reduces the burden and risk of respiratory adverse events in the post-operative period. However, both patients affected by chronic obstructive pulmonary disease (COPD) and chest wall disorders and/or neuromuscular diseases may experience the development or the worsening of respiratory failure, even during surgery performed under NA; this latter negatively affects the function of accessory respiratory muscles, resulting in a blunted central response to hypercapnia and possibly in an exacerbation of cardiac dysfunction (NA-induced relative hypovolemia). According to European Respiratory Society (ERS) and American Thoracic Society (ATS) guidelines, non-invasive ventilation (NIV) is effective in the post-operative period for the treatment of both impaired pulmonary gas exchange and ventilation, while the intra-operative use of NIV in association with NA is just anecdotally reported in the literature. Whilst NIV does not assure a protected patent airway and requires the patient’s cooperation, it is a handy tool during surgery under NA: NIV is reported to be successful for treatment of acute respiratory failure; it may be delivered through the patient’s home ventilator, may reverse hypoventilation induced by sedatives or inadvertent spread of anaesthetic up to cervical dermatomes, and allow the avoidance of intubation in patients affected by chronic respiratory failure, prolonging the time of non-invasiveness of respiratory support (i.e., neuromuscular patients needing surgery). All these advantages could make NIV preferable to oxygen in carefully selected patients.